Multinational firm strategy and global poverty alleviation: frameworks and possibilitiesfor building shared commitment - Chatterjee, Samir Ranjan (Sage Publications India Pty Ltd, 2009)
This article is a narrative exploration of ways to strengthen and deepen the MBA curriculum for the future. We argue that interdisciplinary approaches including anthropology, sociology, and the humanities into the curriculum will give a broader-based understanding of the complexities of ethical management and leadership. It is important to educate students not merely to maximize profits but also to face issues such as global sustainability, global prosperity, corporate social responsibility, and other challenges of being a global player. The humanities and social sciences in addition to the traditional MBA curriculum provide us with auxiliary tools for more complex problem solving. These broader dimensions should be integrated into every course to provide a robust grounding for our students. It provides our new MBA graduates with the requisites to face emerging challenges in the workplace today and our global future.